Simplify (x - y + 1) - (x + y - 1).

Question|Asked by elijahmyson

Asked 9/19/2014 9:31:58 AM

Updated 9/21/2014 11:57:36 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Flagged by jeifunk [9/21/2014 11:56:11 PM], Edited by jeifunk [9/21/2014 11:57:33 PM], Unflagged by jeifunk [9/21/2014 11:57:34 PM], Confirmed by jeifunk [9/21/2014 11:57:36 PM]

= 2 - 2y

= 5h - 3k

selymi|Points 16691|

Question|Asked by elijahmyson

Asked 9/19/2014 9:31:58 AM

Updated 9/21/2014 11:57:36 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Flagged by jeifunk [9/21/2014 11:56:11 PM], Edited by jeifunk [9/21/2014 11:57:33 PM], Unflagged by jeifunk [9/21/2014 11:57:34 PM], Confirmed by jeifunk [9/21/2014 11:57:36 PM]

Rating

8

{n - 1 - [n - 1 - (n - 1)]}

= n - 1 - (n - 1 - n + 1)

= n - 1 - 0

= n - 1

= n - 1 - (n - 1 - n + 1)

= n - 1 - 0

= n - 1

Added 9/21/2014 8:07:02 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/21/2014 11:55:50 PM]

Simplify 2m - [n - (m - 2n)]. **Weegy:** 2m - [n - (m - 2n)]
= 2m - (3n - m)
= 3m - 3n (More)

Question

Expert Answered

Updated 9/12/2014 9:57:22 AM

0 Answers/Comments

Simplify 2m - [n - (m - 2n)]. **Weegy:** 2m - [n - (m - 2n)] = 3m - 3n **User:** Simplify -(-2a + 13) + (-9a - 2) - (-7a - 3). **Weegy:** Simplify -(-2a + 13) + (-9a - 2) - (-7a - 3). -12 **User:** Simplify 3j - {2k - [5h - (3j + k)]}. **Weegy:** 3j - {2k - [5h - (3j + k)]} = 5h - 3k **User:** Simplify (3x + 5) + (2x - 9) - (4x + 3). (More)

Question|Asked by elijahmyson

Not Answered

Updated 9/22/2014 10:34:19 AM

2 Answers/Comments

Simplify (x - y + 1) - (x + y - 1).

Question

Not Answered

Updated 9/19/2014 1:50:44 PM

1 Answer/Comment

(x - y + 1) - (x + y - 1)

= (x - y + 1) + (-x - y + 1)

= -2y + 2

= (x - y + 1) + (-x - y + 1)

= -2y + 2

Added 9/19/2014 1:50:44 PM

This answer has been confirmed as correct and helpful.

How do I Simplify (3x + 5) + (2x - 9) - (4x + 3) **Weegy:** (3x + 5) + (2x - 9) - (4x + 3) = (5x - 4) - (4x + 3) = (5x - 4) + (-4x - 3) = x - 7 (More)

Question

Not Answered

Updated 9/19/2014 1:52:29 PM

0 Answers/Comments

32,561,968

questions answered

There are no comments.